PENGARUH PROFITABILITAS, SOLVABILITAS DAN UKURAN PERUSAHAAN TERHADAP RETURN SAHAM PADA PERUSAHAAN SEKTOR CONSUMER NON- CYCLICALS YANG TERDAFTAR DI BURSA EFEK INDONESIA - Musa Siagian; Muhammad Asrin Jazuli; Jojor Lisbet Sibarani; Eli Safrida (Jurnal Akuntansi dan Bisnis, 2026)
This research aims to empirically prove the influence of profitability, solvency, and company size on stock returns in consumer non-cyclical sector companies listed on the Indonesia Stock Exchange. The sampling technique in this research is the purposive sampling method. The sample in this research consisted of 29 companies and 116 observation data. The data collection technique used in this research is documentation techniques. Data was collected based on annual reports and audited financial statements of consumer non-cyclical sector companies for the period 2020–2023, which can be accessed via the official website of the Indonesia Stock Exchange. The data was processed and analyzed using multiple linear regression analysis techniques with SPSS version 25 software. The results of this research show that profitability has a positive effect on stock returns, solvability has a positive effect on stock returns, while company size has no effect on stock returns